The Impact of Extra-Weighted Exercises in Improving Physical Abilities Towards Accurate Ace Shots in Volleyball Game - Ethar Hamdi Abdulrahman; Adnan Fad’us Omar (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aimed to prepare special exercises to develop some of the physical and skill aspects of volleyballplayers, and to pay attention to the use of additional weights and thus stand on one of the main and importantaspects and its money in the role of preparing players in accordance with the requirements of the gameand to identify the effect of these exercises using different resistances in some physical abilities and myskills Serving and crushing volleyball players, and the research sample consisted of (12) players in thespecialized training center for volleyball aged (15-17) years and in a deliberate manner for the academic year(2019-2020), and the researchers concluded that the training curriculum has a positive effect on developingphysical abilities And skill, which indicates the impact of the training curriculum prepared by the researchersin developing these abilities. As the research objectives are achieved, the researchers recommended makinguse of the prepared training curriculum in building similar approaches to develop some physical and skillfulabilities of volleyball players.